2004
DOI: 10.3354/meps268231
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral mechanisms underlying the refuge value of benthic habitat structure for two flatfishes with differing anti-predator strategies

Abstract: Juvenile flatfish habitat is usually modeled on the basis of sediment grain-size, depth and temperature. Recent evidence indicates that some juvenile flatfishes associate with emergent structures such as sponge, shell and other biogenic and bed-form features of otherwise low-relief shelf habitats. In laboratory experiments we examined the habitat preference and effects of habitat structure upon predation vulnerability of sub-yearling (Age-0) Pacific halibut Hippoglossus stenolepis and northern rock sole Lepido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 55 publications
(61 reference statements)
2
73
0
Order By: Relevance
“…Even with the ability to compensate for periods of reduced growth, delayed halibut face considerable obstacles to survival and recruitment, as the estimated time to complete compensation was at least 3 times the duration of the growth reduction. Further, the increased foraging activity during the growth compensation period may result in additional predation risk (Ryer et al 2004). Finally, the diversion of assimilated energy from lipid storage to growth may increase vulnerability to starvation during subsequent periods of prey scarcity.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the ability to compensate for periods of reduced growth, delayed halibut face considerable obstacles to survival and recruitment, as the estimated time to complete compensation was at least 3 times the duration of the growth reduction. Further, the increased foraging activity during the growth compensation period may result in additional predation risk (Ryer et al 2004). Finally, the diversion of assimilated energy from lipid storage to growth may increase vulnerability to starvation during subsequent periods of prey scarcity.…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile flatfish often demonstrate avoidance response to other approaching fish (Ryer et al 2004), and it is possible that the flatfish observed in this study move in order to simply avoid such interactions. In no instances did we observe territoriality or other agonistic behavior (e.g.…”
Section: Density-dependent Habitat Selectionmentioning
confidence: 97%
“…To date there have been few explicit tests of DDHS in marine fish species (juvenile pollock Pollachius virens, Rangley & Kramer 1998; juvenile cod Gadus morhua and G. ogac, Laurel et al 2004; gag Mycteroperca microlepsis, Lindberg et al 2006) despite the multitude of studies describing area-abundance relationships in marine environments (see Shepherd & Litvak 2004 for review). In flatfish, fine grained sand substrates are preferred over relatively coarser grained substrates (Stoner & Ottmar 2003), most likely because flatfish are more capable of burying in such habitats as a means of reducing predation (Ryer et al 2004; although see Manderson et al 2000) or finding food (Livingston 1987). The increased use of coarse grained habitats at higher densities suggests the fitness benefits of sand (e.g.…”
Section: Density-dependent Habitat Selectionmentioning
confidence: 99%
“…Camouflage is also a primary reason for substrate choice in many animals that have fixed, or slowly changing, body patterns across the animal kingdom (Cott 1940), from insects to arachnids and crustaceans to vertebrates (e.g. mayfly larvae, Tikkanen et al 2000;spiders, Heiling et al 2005; tiger prawns, Kenyon et al 2003;sculpin, Brown 1991;weedy seadragons, Sanchez-Camara et al 2006;flatfish, Moles & Norcross 1995;Stoner & Ottmar 2003;Stoner & Titgen 2003;Ryer et al 2004Ryer et al , 2008. Moving to the wrong substrate may render an animal with a fixed body pattern conspicuous (Merilaita et al 1999).…”
Section: Introductionmentioning
confidence: 99%